2015
DOI: 10.1186/s12917-015-0360-6
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide derived from the rumen down-regulates stearoyl-CoA desaturase 1 expression and alters fatty acid composition in the liver of dairy cows fed a high-concentrate diet

Abstract: BackgroundDairy cows are often fed a high-concentrate diet to meet lactating demands, yet long-term concentrate feeding induces subacute ruminal acidosis (SARA) and leads to a decrease in milk fat. Stearoyl-CoA desaturase1 (SCD1) participates in fatty acid biosynthesis in the liver of lactating ruminants. Here, we conducted this study to investigate the impact of lipopolysaccharide derived from the rumen on SCD1 expression and on fatty acid composition in the liver of dairy cows fed a high-concentrate diet. Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 61 publications
4
49
2
Order By: Relevance
“…The results of ruminal pH fed a high concentrate diet were published previously by Xu et al [33] and he confirmed the presence of SARA by measuring the ruminal pH at different time intervals. In this study, consuming a high-concentrate diet (HC group) for 18 weeks resulted in a significant decline in ruminal pH (<5.6) than that in the LC group ( p  < 0.05) and lasted for more than three hours [2].…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The results of ruminal pH fed a high concentrate diet were published previously by Xu et al [33] and he confirmed the presence of SARA by measuring the ruminal pH at different time intervals. In this study, consuming a high-concentrate diet (HC group) for 18 weeks resulted in a significant decline in ruminal pH (<5.6) than that in the LC group ( p  < 0.05) and lasted for more than three hours [2].…”
Section: Resultssupporting
confidence: 78%
“…Conclusively, LPS activates TLR4-NF-κB signalling. Together with the existing study and the previous reports [33, 37], the protein expressions of NF-κB (p65) and p-p65 were magnified in the HC group.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The production of long-chain fatty acids that activate Pparγ may have been enhanced in cattle fed the concentrate or vitamin A-deficient diet. The dietary roughage to concentrate ratio affected the fatty acid composition in bovine WAT; plasma concentration of long-chain fatty acid was generally decreased by feeding high concentrate diet in cattle, but the concentrations of C22:0 and C22:1 were increased (Xu et al 2015). Furthermore, the vitamin A status may affect the fatty acid profile in the intramuscular fat of beef cattle by modulating Δ 9 -desaturase activity potentially (Smith et al 2009).…”
Section: Ucp3mentioning
confidence: 99%
“…In the dairy industry, it is currently common practice to feed a high-concentrate (HC) diet to lactating cows or goats to meet their energy requirements to support high milk production. However, long-term high concentrate feeding is harmful to the health of ruminants and leads to a decrease in milk yield [1]. It was reported that feeding of HC diets to lactating cows causes a decline in the rumen pH if organic acids, such as volatile fatty acid (VFA) and lactic acid, accumulate in the rumen[2].…”
Section: Introductionmentioning
confidence: 99%